The impact of lactoferrin with different levels of metal saturation on the intestinal epithelial barrier function and mucosal inflammation - Majka, Grzegorz (Biometals, 2016)
Translocation of bacteria, primarily Gram-negative pathogenic flora, from the intestinal lumen into the circulatory system leads to sepsis. In newborns, and especially very low birth weight infants, sepsis is a major cause of morbidity and mortality. The results of recently conducted clinical trials suggest that lactoferrin, an iron-binding protein that is abundant in mammalian colostrum and milk, may be an effective agent in preventing sepsis in newborns. However, despite numerous basic studies on lactoferrin, very little is known about how metal saturation of this protein affects a host’s health. Therefore, the main objective of this study was to elucidate how iron-depleted, iron-saturated, and manganese-saturated forms of lactoferrin regulate intestinal barrier function via interactions with epithelial cells and macrophages. For these studies, a human intestinal epithelial cell line, Caco-2, was used. In this model, none of the tested lactoferrin forms induced higher levels of apoptosis or necrosis. There was also no change in the production of tight junction proteins regardless of lactoferrin metal saturation status. None of the tested forms induced a pro-inflammatory response in Caco-2 cells or in macrophages either. However, the various lactoferrin forms did effectively inhibit the pro-inflammatory response in macrophages that were activated with lipopolysaccharide with the most potent effect observed for apolactoferrin. Lactoferrin that was not bound to its cognate receptor was able to bind and neutralize lipopolysaccharide. Lactoferrin was also able to neutralize microbial-derived antigens, thereby potentially reducing their pro-inflammatory effect. Therefore, we hypothesize that lactoferrin supplementation is a relevant strategy for preventing sepsis.